Seasonal variations and shared latrine cleaning practices in the slums of Kampala city, Uganda - Japheth Kwiringira; Peter Atekyereza; Charles Niwagaba; Robert Kabumbuli; Charles Rwabukwali; Robinah Kulabako; Isabel Günther (BMC, 2016)
Abstract Background The effect of seasons on health outcomes is a reflection on the status of public health and the state of development in a given society. Evidence shows that in Sub-Saharan Africa, most infectious diseases flourish during the wet months of the year; while human activities in a context of constrained choices in life exacerbate the effects of seasons on human health. The paper argues that, the wet season and when human activities are at their peak, sanitation is most dire poor slum populations. Methods A shared latrine cleaning observation was undertaken over a period of 6 months in the slums of Kampala city. Data was collected through facility observations, user group meetings, Focus group discussions and, key informant interviews. The photos of the observed sanitation facilities were taken and assessed for facility cleanliness or dirt. Shared latrine pictures, observations, Focus Group Discussion, community meetings and key informant interviews were analysed and subjected to an analysis over the wet, dry and human activity cycles before a facility was categorised as either 'dirty' or 'clean'. Results Human activity cycles also referred to as socio-economic seasons were, school days, holidays, weekends and market days. These have been called 'impure' seasons, while the 'pure' seasons were the wet and dry months: improved and unimproved facilities were negatively affected by the wet seasons and the peak seasons of human activity. Wet seasons were associated with, mud and stagnant water, flooding pits and a repugnant smell from the latrine cubicle which made cleaning difficult. During the dry season, latrines became relatively cleaner than during the wet season. The presence of many child(ren) users during school days as well as the influx of market goers for the roadside weekly markets compromised the cleaning outcomes for these shared sanitation facilities. Conclusion Shared latrine cleaning in slums is impacted by seasonal variations related to weather conditions and human activity. The wet seasons made the already bad sanitation situation worse. The seasonal fluctuations in the state of shared slum sanitation relate to a wider malaise in the population and an implied capacity deficit among urban authorities. Poor sanitation in slums is part of a broader urban mismanagement conundrum pointing towards the urgent need for multiple interventions aimed at improving the general urban living conditions well beyond sanitation.